The AKT1 gene is associated with attention and brain morphology in schizophrenia. (March 2013) - Ohi, Kazutaka; Hashimoto, Ryota; Yasuda, Yuka; Fukumoto, Motoyuki; Nemoto, Kiyotaka; Ohnishi, Takashi; Yamamori, Hidenaga; Takahashi, Hidetoshi; Iike, Naomi; Kamino, Kouzin; Yoshida, Tetsuhiko; Azechi, Michiyo; et al.
Abstract Objectives. A meta-analysis of the associations between genetic variants in the AKT1 gene and schizophrenia found that a single nucleotide polymorphism (SNP5; rs2494732) was associated with schizophrenia in Asian populations. Methods. In this study, we investigated the effects of this SNP on memory and attentional performance and brain structure using magnetic resonance imaging in a Japanese population (117 patients with schizophrenia and 189 healthy subjects). Results. The memory performance, particularly attention/concentration score, measured by the Wechsler Memory Scale-Revised in A carriers of SNP5, which was found to be enriched in patients with schizophrenia, was lower than that in individuals with the G/G genotype. We confirmed the association of the SNP with attentional performance using the Continuous Performance Test, which assessed sustained attention and vigilance of attentional function. Patients with A allele demonstrated lower attentional performance than patients with the G/G genotype. Patients with the A allele had smaller gray matter volumes in the right inferior parietal lobule related to attentional processes and in the frontostriatal region related to different SNPs in AKT1 than patients with the G/G genotype. Conclusions. Our results suggest that a genetic variant of AKT1 might be associated with attentional deficits and brain morphological vulnerability in patients with schizophrenia.